Multi-structure functional epoxy resin microsphere as well as preparation method and reinforcing and toughening application thereof

By preparing multi-structure functional epoxy resin microspheres, using their chemical bonding and mechanical interlocking with epoxy resin and cement, the problem of difficulty in simultaneously improving the toughness and strength of epoxy resin and cement in the prior art is solved, and the simultaneous toughening and strengthening effect of the material is achieved.

CN119570072AActive Publication Date: 2025-03-07BEIJING UNIV OF CHEM TECH +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411702471.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

During the toughening and modification process of existing epoxy resins and cements, it is difficult to improve toughness and strength at the same time, and the interface between particles and the matrix is ​​weak, resulting in a decrease in strength.

Method used

A multi-structure functional epoxy resin microsphere is prepared by the "one-pot method" to form non-porous, porous, hollow, raspberry-shaped or semi-empty snowman-shaped microspheres. The surface of the microspheres contains amino, hydroxyl or epoxy groups, which can be chemically bonded with epoxy resin and cement, and improve the toughness and strength of the material through mechanical interlocking.

Benefits of technology

The impact strength, tensile strength and elongation of break of epoxy resin are significantly improved, as well as the compressive strength, flexural strength, ultimate strain and toughness modulus of cement stone, achieving simultaneous toughening enhancement of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153689320000141
    Figure BDA0005153689320000141
  • Figure BDA0005153689320000151
    Figure BDA0005153689320000151
  • Figure BDA0005153689320000152
    Figure BDA0005153689320000152
Patent Text Reader

Abstract

The invention discloses a multi-structure functional epoxy resin microsphere as well as a preparation method and reinforcing and toughening application thereof. The preparation method of the epoxy resin microspheres comprises the following steps: reacting a mixture A, a mixture B and a mixture C under the action of a catalyst to obtain the multi-structure functional epoxy resin microspheres, the mixture A is prepared by dispersing or dissolving a surfactant in a solvent A, or is prepared by dispersing or dissolving a surfactant and a stabilizer in the solvent A; the mixture B is prepared by mixing and heating epoxy resin and a solvent B; and the mixture C is prepared by dissolving a curing agent in a solvent C. The epoxy resin microspheres are prepared by adopting a one-pot method, the preparation process is simple, the obtained microspheres are highly crosslinked, the surfaces of the microspheres contain amino, epoxy or hydroxyl functional groups, and the microspheres have non-porous, porous, hollow, raspberry-shaped or semi-hollow snowman-shaped multi-structures and can be used for toughening and reinforcing epoxy resin and cement at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of epoxy resins, and in particular relates to multi-structural functional epoxy resin microspheres and a preparation method thereof, and the reinforcing and toughening application thereof in epoxy resins and cement. Background Art

[0002] Epoxy resin has a highly cross-linked network structure, so it has excellent properties such as high strength, high thermal stability, and corrosion resistance. At the same time, it has the problems of insufficient toughness and high brittleness, which limits its wide application in the fields of construction, aerospace, electronics, etc. Similarly, cement used in oil wells has high strength, but it also has the problems of high brittleness and small deformation, which easily causes microcracks and failure in cementing. In order to improve the toughness of epoxy resin and cement, people add inorganic, organic hard particles or organic elastic particles to them, but this method still has the problem of weak interface bonding between particles and matrix, and the strength decreases while the toughness increases. The use of epoxy microspheres to self-toughen the epoxy resin substrate avoids the interface problem, but hard epoxy microspheres with a high degree of cross-linking (Tg>200℃) are required to improve the toughness without a significant decrease in strength. Considering the excellent properties of epoxy resin, there have been reports on the use of elastic and tough epoxy particle powder and elastic and tough core (epoxy resin / polyamide)-hard shell (SiO2) composite microspheres to toughen cement. However, while the above methods improve the toughness and deformation capacity of cement paste, they will also lead to a decrease in elastic modulus and compressive strength. How to effectively and simultaneously improve the toughness and strength of cement paste is still a technical problem that needs to be solved urgently.

[0003] Epoxy resin microspheres are thermosetting polymer microspheres formed by reacting epoxy resin and curing agent as monomers. Currently, they can be prepared by emulsion polymerization, phase inversion emulsion polymerization, suspension polymerization, dispersion polymerization and precipitation polymerization (reaction induced phase separation). For example, epoxy resin, active diluent, liquid imidazole curing agent (Chinese invention patent CN101074311A) are used for emulsion polymerization in an aqueous phase system containing an emulsifier; epoxy resin, diluent and amine curing agent are dispersed in water containing polyvinyl alcohol (PVA) and sodium dodecyl sulfonate (SDS) as dispersant stabilizers for suspension polymerization; epoxy resin, curing agent, organic solvent (methyl isobutyl ketone), emulsifier (hexadecyl trimethyl ammonium bromide, Span 80), and liquid rubber are mixed evenly, pre-cured, and then the resulting product is stirred. While slowly adding deionized water to achieve phase inversion and stabilize the emulsion, and then continue to react completely (Chinese invention patent CN108129605A) to obtain epoxy resin microspheres; using the phase inversion emulsion polymerization method, in situ adding toughening monomers with good flexibility and good aging resistance such as acrylates, double-bond organic siloxanes, oligomer polyamide 650, etc. in the epoxy resin curing system to prepare epoxy resin microsphere materials with good flexibility (Chinese invention patents CN107880492A, CN108047653A); or using the phase inversion emulsification technology to obtain epoxy resin water / oil (epoxy) / water, or water / epoxy / ethylene glycol (Chinese invention patent CN102850521A) double emulsions, and then reacting with a small amount of curing agent and removing water to obtain porous or hollow epoxy resin microspheres. These microspheres have good impact resistance, but low strength. When used for epoxy toughening, good toughening effect is often accompanied by a decrease in strength.

[0004] The epoxy resin and curing agent are subjected to precipitation polymerization or dispersion polymerization in epoxy soybean oil and liquid crystal, or are evenly mixed with thermoplastic polymers such as polyester, polyether diol (such as polypropylene glycol PPG600), polytetramethylene glycol (PTG), polylactic acid (PCL), etc., and phase separation is induced during the curing and cross-linking reaction to form hard (Tg>200°C) epoxy resin microspheres with narrow particle size distribution, smooth surface and high cross-linking. However, the above preparation process is complicated, especially the need to use a large amount of organic solvent to elute the microspheres, and the yield of the microspheres is not high, which affects the promotion and use. Summary of the invention

[0005] The purpose of the present invention is to provide a multi-structure functional epoxy resin microsphere and a preparation method thereof in view of the problem that it is not easy to effectively improve the toughness and strength in the toughening modification process of epoxy resin and cement substrates. The present invention also provides the application of the obtained microsphere in the toughening and strengthening of epoxy resin and cement. The present invention is a "one-pot method" for preparing epoxy resin microspheres, the process is simple, the microspheres are highly cross-linked (high Tg), and the surface contains amino, epoxy, or hydroxyl functional groups. The epoxy resin microspheres with multi-structures such as non-porous, porous, hollow, raspberry-shaped or half-empty snowman-shaped can be prepared. The obtained microspheres The microspheres can be firmly bonded to epoxy and cement substrates through chemical bonding via surface functional groups. The holes and protrusions on the microsphere surface can form a mechanical interlock with the substrate, thereby simultaneously improving the toughness and strength of the material by inducing interface silver streaks and exerting a pinning effect. Test results show that the microspheres obtained by the present invention can be used to toughen epoxy resin, thereby significantly improving the impact strength, tensile strength and elongation at break of epoxy resin. The microspheres obtained by the present invention can be used to toughen cement, thereby significantly improving the compressive strength, flexural strength, ultimate strain and toughness modulus of cement stone.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] In a first aspect, the present invention provides a method for preparing epoxy resin microspheres, comprising the following steps:

[0008] The mixture A, the mixture B and the mixture C are reacted under the action of a catalyst to obtain the multi-structure functional epoxy resin microspheres;

[0009] The mixture A is prepared by dispersing or dissolving a surfactant in a solvent A, or by dispersing or dissolving a surfactant and a stabilizer in a solvent A;

[0010] The mixture B is prepared by mixing epoxy resin and solvent B and then heating;

[0011] The mixture C is prepared by dissolving a curing agent in a solvent C.

[0012] In the above-mentioned preparation method of epoxy resin microspheres, the multi-structure functional epoxy resin microspheres include epoxy resin microspheres with non-porous, porous, hollow, raspberry-shaped or half-hollow snowman-shaped structures;

[0013] The surface of the epoxy resin microspheres contains one or two of amino, hydroxyl and epoxy groups, but not both amino and epoxy groups. For example, if it contains amino, hydroxyl or epoxy and hydroxyl groups, the residual groups on the surface of the microspheres after the reaction are affected by the ratio of epoxy and curing agent;

[0014] The particle size of the multi-structure functional epoxy resin microspheres is 7.3 to 1116 μm, specifically the average particle size analyzed by a laser particle size analyzer;

[0015] The glass transition temperature Tg of the multi-structure functional epoxy resin microspheres is 124-168°C.

[0016] In the above-mentioned method for preparing epoxy resin microspheres, the epoxy resin is selected from at least one of a diepoxy monomer, a triepoxy monomer and a tetraepoxy monomer;

[0017] Based on 100 parts by mass of the epoxy resin, the mass fraction of the triepoxy monomer or the tetraepoxy monomer is 0 to 10 parts, including but not limited to 0 parts, 10 parts or 5 parts;

[0018] The diepoxy monomer is preferably bisphenol A diglycidyl ether E51 (epoxy resin E51) or bisphenol A diglycidyl ether E44 (epoxy resin E44);

[0019] The triepoxy monomer is preferably trimethylolpropane triglycidyl ether (TMTGE);

[0020] The tetraepoxy monomer is preferably 4,4-diaminodiphenylmethane tetraglycidylamine (TGMDA).

[0021] In the above-mentioned preparation method of epoxy resin microspheres, the surfactant is a nonionic surfactant, including one of polyvinyl pyrrolidone (such as PVP30K), polyvinyl alcohol (such as PEG200), and benzene resin;

[0022] When only a surfactant is added to the mixture A, the mass fraction of the surfactant is 35 to 140 parts, including but not limited to 140 parts, 35 parts or 80 parts, based on 100 parts by mass of the epoxy resin;

[0023] The stabilizer is a SiO2 nanoparticle or nanosheet having amino groups, epoxy groups or hydroxyl groups on the surface;

[0024] When a surfactant and a stabilizer are added to the mixture A at the same time, based on 100 parts by mass of the epoxy resin, the mass fractions of the surfactant and the stabilizer are 35 to 140 parts, including but not limited to 70 parts, and the mass fraction of the stabilizer is 0.08 to 1.6 parts, including but not limited to 0.08 parts.

[0025] In the above-mentioned preparation method of epoxy resin microspheres, the curing agent is a polyamine curing agent, which is one or more selected from vinylamine, polyetheramine, alicyclic amine, aromatic amine and a disulfide bond-containing curing agent;

[0026] The acetamide is preferably triethylenetetramine (TETA);

[0027] The polyetheramine is preferably polypropylene glycol di(2-aminopropyl) ether (polyetheramine D230);

[0028] The alicyclic amine is preferably isophoronediamine (IPDA);

[0029] The aromatic amine is preferably 4,4'-diaminodiphenylmethane (DDM) or diethyltoluenediamine (DETDA);

[0030] The disulfide bond-containing curing agent is preferably 4,4' dithiodiphenylamine (DTDA);

[0031] Based on 100 parts by mass of the epoxy resin, the mass of the curing agent is 15 to 35 parts, including but not limited to 35 parts, 15 parts or 25 parts.

[0032] In the above-mentioned method for preparing epoxy resin microspheres, the solvent A is an organic solvent a and / or water;

[0033] The solvent B is an organic solvent b and / or water;

[0034] The solvent C is an organic solvent c and / or water;

[0035] The organic solvent a, the organic solvent b and the organic solvent c are organic alcohols, ketones or alkanes; the organic alcohol is preferably ethanol; the ketone is preferably acetone; the alkane is preferably n-hexane;

[0036] In the solvent A, based on 100 parts by mass of the epoxy resin, the mass fraction of the organic solvent a is 0 to 493 parts, and the mass fraction of water is 0 to 625 parts, but both are not 0 at the same time;

[0037] In the solvent b, based on 100 parts by mass of the epoxy resin, the mass fraction of the organic solvent b is 78 to 493 parts, and the mass fraction of water is 0 to 625 parts;

[0038] In the solvent c, based on 100 parts by mass of the epoxy resin, the mass of the organic solvent c is 78 to 493 parts, and the mass of water is 0 to 625 parts.

[0039] In the above-mentioned preparation method of epoxy resin microspheres, the catalyst is a tertiary amine catalyst, including one of 1,8-diazabicycloundec-7-ene (DBU), benzyldimethylamine (BDMA), and 2,4,6-tris(dimethylaminomethyl)phenol (DMP-30);

[0040] Based on 100 parts by mass of the epoxy resin, the amount of the catalyst used is 1 to 5 parts, including but not limited to 5 parts, 1.25 parts, 2.5 parts, 1.5 parts or 1 part.

[0041] In the above-mentioned method for preparing epoxy resin microspheres, the reaction is carried out under stirring conditions, and the stirring speed is 300 to 500 rpm, such as 500 r / min;

[0042] The reaction temperature is 60-90°C and the reaction time is 4-6h, such as reacting at 90°C or 60°C for 6h;

[0043] The preparation further comprises the following steps after the reaction is completed: centrifuging the reaction solution to collect the solid phase product, then washing with ethanol, centrifuging and drying.

[0044] In a second aspect, the present invention protects the epoxy resin microspheres obtained by the preparation method of the epoxy resin microspheres described in any one of the above items.

[0045] In a third aspect, the present invention protects the use of the epoxy resin microspheres in toughening and strengthening epoxy resin or cement.

[0046] In the above application, the toughening and strengthening in the epoxy resin is reflected in simultaneously improving the toughness and strength of the epoxy resin, specifically, simultaneously improving the impact strength, tensile strength and elongation at break of the epoxy resin;

[0047] The toughening and strengthening in cement is reflected in simultaneously improving the toughness and strength of cement paste, and specifically in simultaneously improving the compressive strength, flexural strength, ultimate strain and toughness modulus of cement paste.

[0048] In the above application, the toughening and strengthening in epoxy resin includes the following steps: preparing modified epoxy resin from epoxy resin monomer, epoxy resin microspheres and curing agent.

[0049] Preferably, based on 100 parts by mass of the epoxy resin monomer, the mass fraction of the epoxy resin microspheres is 0.5 to 8 parts, including but not limited to 5 parts, 2 parts, 4 parts or 0.5 parts;

[0050] As a test example, based on 100 parts by mass of the epoxy resin monomer, the mass of the curing agent is 15 to 35 parts, including but not limited to 26 parts or 35 parts;

[0051] As a test example, the preparation steps are as follows: add the obtained microspheres to the epoxy resin monomer, heat to 70°C, stir for 2 hours, rotate at 120 r / min, add a curing agent, stir, and obtain an epoxy resin reaction liquid; pour the epoxy resin reaction liquid into a 80°C preheated mold, heat and cure at 80°C×1h+100°C×1h+130°C×1h, and naturally cool to room temperature to obtain a modified epoxy resin.

[0052] In the above application, the toughening and strengthening in cement comprises the following steps: cement ash, the epoxy resin microspheres and water are made into cement slurry, and the cement slurry is cured to obtain cement stone.

[0053] Preferably, based on 100 parts by mass of cement ash, the mass fraction of the epoxy resin microspheres is 5 to 10 parts, including but not limited to 10 parts, 5 parts, 8 parts or 6 parts;

[0054] As a test example, the preparation steps are as follows: add the epoxy resin microspheres to the G-grade cement ash, add water, shake and homogenize to obtain cement slurry; put the cement slurry into a hydrothermal kettle, cure in a 95°C oven for 1 day, and then cure in a 95°C constant temperature water for 6 days.

[0055] The present invention has the following beneficial effects:

[0056] (1) The present invention can prepare functional epoxy resin microspheres with multiple structures (non-porous, porous, hollow, raspberry-shaped, half-empty snowman-shaped) and containing amino, hydroxyl or epoxy on the surface by a "one-pot method", and the process is simple;

[0057] (2) The epoxy resin is toughened by using the microspheres obtained by the present invention, which can significantly improve the impact strength, tensile strength and elongation at break of the epoxy resin at the same time. Compared with the blank sample without epoxy resin microspheres, the impact strength of the epoxy resin sample strips with epoxy resin microspheres added is increased by 23-70%, the tensile strength is increased by 19-35%, and the elongation at break is increased by 43-107%; the epoxy resin microspheres of the present invention can simultaneously improve the toughness and strength of the epoxy resin, and achieve simultaneous toughening and strengthening of the epoxy resin;

[0058] (3) The microspheres obtained by the present invention are used to toughen cement, which can significantly improve the compressive strength, flexural strength, ultimate strain and toughness modulus of cement paste at the same time. Compared with blank cement paste without epoxy microspheres, the compressive strength of the cement paste prepared by adding epoxy microspheres is increased by 16-40%, the flexural strength is increased by 29-57%, the ultimate strain is increased by 113-193%, and the toughness modulus is increased by 21-72%; the epoxy resin microspheres of the present invention can simultaneously improve the toughness and strength of cement, and achieve simultaneous toughening and strengthening of cement. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 (a) is the SEM photo of the non-porous epoxy microspheres prepared in Examples 1, 4, and 5. Figure 1 (b) are non-porous epoxy microspheres prepared in Examples 2 and 3;

[0060] Figure 2 (a) is a SEM photo of the raspberry-shaped epoxy microspheres prepared in Example 6, Figure 2 (b) is a SEM photo of raspberry-shaped epoxy microspheres prepared in Example 8;

[0061] Figure 3 This is a SEM photo of the porous epoxy microspheres prepared in Example 7;

[0062] Figure 4 This is a SEM photo of the half-air snowman-shaped epoxy microspheres prepared in Example 9;

[0063] Figure 5 (a) and (b) are SEM photos of hollow epoxy microspheres prepared in Example 10;

[0064] Figure 6 This is a SEM photograph of the raspberry-shaped hollow epoxy microspheres prepared in Example 11. DETAILED DESCRIPTION

[0065] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.

[0066] The methods used in the following examples, unless otherwise specified, are all conventional methods, carried out according to the techniques or conditions described in the literature in the art or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial sources.

[0067] The SiO2 nanoparticles with functional groups on the surface in the following embodiments are from Henan Nanomaterial Engineering Technology Research Center, DL-A20, 20nm; the SiO2 nanosheets with functional groups on the surface are from Henan Nanomaterial Engineering Technology Research Center, DL-NP-10, 2×30μm×10nm.

[0068] The surfactant PVP in the following examples is polyvinyl pyrrolidone PVP30K, MREDA M056871, PEG is polyvinyl alcohol PEG200, AC13798, and benzene maleic anhydride resin is styrene maleic anhydride resin, J-3000.

[0069] In the following examples, the particle morphology was observed using a scanning electron microscope (SEM); the particle size of the epoxy microspheres was measured using a Mastersizer 2000 laser diffraction particle size analyzer (Malvern Instruments Ltd.); and the glass transition temperature (Tg) of the epoxy resin microspheres was tested using differential scanning calorimetry (DSC).

[0070] Example 1

[0071] This embodiment provides the preparation of multi-structure functional epoxy resin microspheres and their toughening and strengthening effects in epoxy resin.

[0072] 1. Preparation

[0073] Preparation of epoxy resin microspheres, the specific steps are as follows:

[0074] S1. Add 5.6 g PVP and 20 mL ethanol to a centrifuge tube to obtain mixture A; add 4 g epoxy resin E51 to a centrifuge tube, add 8 mL ethanol and mix, and heat to 50° C. to obtain mixture B; add 1.4 g curing agent DDM to a centrifuge tube, add 12 mL ethanol to dissolve DDM, and obtain mixture C;

[0075] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 1 (a) shows non-porous epoxy microspheres.

[0076] In this embodiment, the average particle size of the microspheres analyzed by a laser particle size analyzer is 11.9 μm, and the glass transition temperature thereof measured by DSC is 164° C.

[0077] 2. Epoxy resin toughening and strengthening

[0078] The epoxy resin microspheres prepared above are used to toughen the epoxy resin, and the specific steps are as follows:

[0079] Add 1.0 g of the obtained microspheres to 20 g of E51 monomer, heat to 70°C, stir for 2 h, rotate at 120 r / min, then add 5.2 g of curing agent IPDA and stir for 5 min; pour the prepared epoxy resin reaction liquid into a 80°C preheated mold, put it into an oven, heat and cure at 80°C×1h+100°C×1h+130°C×1h, and naturally cool to room temperature to obtain modified epoxy resin strips.

[0080] According to the requirements of GB / T1040.4-2006, the tensile properties and impact properties of epoxy resin specimens were measured, and 5 samples were tested each time and the average value was taken. The epoxy resin without adding particles was used as a blank sample. The test results are shown in Table 1.

[0081] It can be seen from Table 1 that compared with the blank sample without microspheres, the impact strength of the epoxy resin with microspheres added is increased by 70%, the tensile strength is increased by 35%, and the elongation at break is increased by 107%.

[0082] Example 2

[0083] As in Example 1, in the process of preparing microspheres, the amount of surfactant PVP used is 1.4 g, the amount of curing agent DDM used is 0.6 g, the organic solvent used is acetone, the stirring speed is 300 r / min, the temperature is raised to 60°C for reaction, and then the mixture B and C are added, and the catalyst DBU 0.05 g is added. The specific steps are as follows:

[0084] S1. Add 1.4 g PVP and 20 mL acetone to a centrifuge tube to obtain mixture A; add 4 g epoxy resin E51 to a centrifuge tube, add 8 mL acetone and mix, and heat to 50° C. to obtain mixture B; add 0.6 g curing agent DDM to a centrifuge tube, add 12 mL acetone to dissolve DDM, and obtain mixture C;

[0085] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 300 r / min, heat the water bath to 60° C., then add mixtures B and C, add 0.05 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing epoxy groups, hydroxyl groups, such as attached Figure 1 (b) shows non-porous epoxy microspheres.

[0086] In this embodiment, the average particle size of the obtained microspheres is 247.5 μm, and the glass transition temperature Tg is 124°C.

[0087] As in Example 1, 0.5 g of the obtained microspheres were added to the E51 and IPDA curing system to prepare epoxy resin strips. The specific steps are as follows:

[0088] Add 0.5 g of the obtained microspheres to 20 g of E51 monomer, heat to 70°C, stir for 2 h, rotate at 120 r / min, then add 5.2 g of curing agent IPDA and stir for 5 min; pour the prepared epoxy resin reaction liquid into a 80°C preheated mold, put it into an oven, heat and cure at 80°C×1h+100°C×1h+130°C×1h, and cool naturally to room temperature to obtain modified epoxy resin strips.

[0089] According to the requirements of GB / T1040.4-2006, the tensile properties and impact properties of epoxy resin specimens were measured, and 5 samples were tested each time and the average value was taken. The epoxy resin without adding particles was used as a blank sample. The test results are shown in Table 1.

[0090] It can be seen from Table 1 that, compared with the blank sample without microspheres, the impact strength of the epoxy resin with microspheres added is increased by 39%, the tensile strength is increased by 14%, and the elongation at break is increased by 48%.

[0091] Example 3

[0092] As in Example 1, in the process of preparing microspheres, the amount of surfactant PVP used is 3.2 g, the amount of curing agent DDM used is 1.4 g, the stirring speed is 300 r / min, the temperature is raised to 80° C. for reaction, and 0.1 g of catalyst DBU is added. The specific steps are as follows:

[0093] S1. Add 3.2 g PVP and 20 mL ethanol to a centrifuge tube to obtain mixture A; add 4 g epoxy resin E51 to a centrifuge tube, add 8 mL ethanol and mix, and heat to 80° C. to obtain mixture B; add 1.4 g curing agent DDM to a centrifuge tube, add 12 mL ethanol to dissolve DDM, and obtain mixture C;

[0094] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 300 r / min, heat the water bath to 60°C, then add mixtures B and C, add 0.1 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 1 (b) shows non-porous epoxy microspheres.

[0095] In this embodiment, the average particle size of the obtained microspheres is 60.5 μm, and the glass transition temperature Tg is 138°C.

[0096] As in Example 1, 1.5 g of the obtained microspheres were added to the E51 and IPDA curing system to prepare epoxy resin strips. The specific steps are as follows:

[0097] Add 1.5 g of the obtained microspheres to 4 g of E51 monomer, heat to 70°C, stir for 2 h, rotate at 120 r / min, then add 5.2 g of curing agent IPDA and stir for 5 min; pour the prepared epoxy resin reaction liquid into a mold preheated at 80°C, put it into an oven, heat and cure at 80°C×1h+100°C×1h+130°C×1h, and naturally cool to room temperature to obtain modified epoxy resin strips.

[0098] According to the requirements of GB / T1040.4-2006, the tensile properties and impact properties of epoxy resin specimens were measured, and 5 samples were tested each time and the average value was taken. The epoxy resin without adding particles was used as a blank sample. The test results are shown in Table 1.

[0099] It can be seen from Table 1 that, compared with the blank sample without microspheres, the impact strength of the epoxy resin with microspheres added is increased by 47%, the tensile strength is increased by 31%, and the elongation at break is increased by 80%.

[0100] Example 4

[0101] As in Example 1, in the process of preparing microspheres, the surfactant used is PEG200 (1.3 g), the epoxy resin is E44 (3.6 g) and TMTGE (0.4 g), the curing agent is TETA (0.6 g), and the catalyst BDMA (0.06 g) is added. The specific steps are as follows:

[0102] S1. Add 1.3 g PEG200 and 20 mL ethanol to a centrifuge tube to obtain mixture A; add 3.6 g epoxy resin E44 and 0.4 g TMTGE to a centrifuge tube, add 8 mL ethanol to mix, and heat to 50° C. to obtain mixture B; add 0.6 g curing agent TETA to a centrifuge tube, add 12 mL ethanol to dissolve TETA, and obtain mixture C;

[0103] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.06 g of catalyst BDMA, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing epoxy, hydroxyl, as attached Figure 1 (a) shows non-porous epoxy microspheres.

[0104] In this embodiment, the average particle size of the obtained microspheres is 7.3 μm and the Tg is 131°C.

[0105] Epoxy resin strips were prepared as in Example 1, and the specific steps were as follows: 0.1 g of the obtained microspheres were added to 20 g of E51 monomer, the temperature was raised to 70°C, and stirred for 2 h at a speed of 120 r / min, and then 5.2 g of curing agent IPDA was added and stirred for 5 min; the prepared epoxy resin reaction solution was poured into a mold preheated at 80°C, placed in an oven, and cured by heating at 80°C × 1h + 100°C × 1h + 130°C × 1h, and naturally cooled to room temperature to obtain modified epoxy resin strips.

[0106] According to the requirements of GB / T1040.4-2006, the tensile properties and impact properties of epoxy resin specimens were measured, and 5 samples were tested each time and the average value was taken. The epoxy resin without adding particles was used as a blank sample. The test results are shown in Table 4.

[0107] It can be seen from Table 1 that compared with the blank sample without microspheres, the impact strength of the epoxy resin with microspheres added is increased by 23%, the tensile strength is increased by 20%, and the elongation at break is increased by 64%.

[0108] Example 5

[0109] As in Example 1, except that in the process of preparing microspheres, the surfactant used is benzene resin (1.4 g), the epoxy resin is E51 (3.8 g) and TGMDA (0.2 g), the amount of curing agent polyetheramine D230 is 1 g, and the catalyst DMP-30 (0.04 g) is added. The specific steps are as follows:

[0110] S1. Add 1.4 g of benzene resin and 20 mL of ethanol to a centrifuge tube to obtain a mixture A; add 3.8 g of epoxy resin E51 and 0.2 g of TGMDA to a centrifuge tube, add 8 mL of ethanol to mix, and heat to 50° C. to obtain a mixture B; add 1 g of curing agent D230 to a centrifuge tube, add 12 mL of ethanol to dissolve D230, and obtain a mixture C;

[0111] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.04 g of catalyst DMP-30, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 1 (a) shows non-porous epoxy microspheres.

[0112] In this embodiment, the average particle size of the microspheres measured by laser particle size analyzer is 23.7 μm, and the glass transition temperature thereof measured by DSC is 137.21°C.

[0113] Epoxy resin strips were prepared as in Example 1, and the specific steps were as follows: 1 g of the obtained microspheres was added to 20 g of E51 monomer, the temperature was raised to 70°C, and stirred for 2 h at a speed of 120 r / min. Then, 5.2 g of curing agent IPDA was added and stirred for 5 min. The prepared epoxy resin reaction solution was poured into a mold preheated at 80°C, placed in an oven, and cured by heating at 80°C × 1h + 100°C × 1h + 130°C × 1h, and naturally cooled to room temperature to obtain modified epoxy resin strips.

[0114] According to the requirements of GB / T1040.4-2006, the tensile properties and impact properties of epoxy resin specimens were measured, and 5 samples were tested each time and the average value was taken. The epoxy resin without adding particles was used as a blank sample. The test results are shown in Table 1.

[0115] As shown in Table 1, compared with the blank sample without microspheres, the impact strength of the epoxy resin with microspheres added is increased by 58%, the tensile strength is increased by 33%, and the elongation at break is increased by 95%.

[0116] Example 6

[0117] As in Example 1, the surfactant used in the microsphere preparation process is PVP (5.6 g), and a stabilizer SiO2 nanoparticle (0.06 g) is added, and a curing agent DTDA (1 g) is used. The specific steps are as follows:

[0118] S1. Add 5.6g PVP and 0.06g stabilizer SiO2 nanoparticles (surface containing amino groups, 20nm) into a centrifuge tube, add 20mL ethanol to obtain mixture A; add 4g epoxy resin E51 into a centrifuge tube, add 8mL ethanol to mix, and heat to 50°C to obtain mixture B; add 1g curing agent DTDA into a centrifuge tube, add 12mL ethanol to dissolve DDM, and obtain mixture C;

[0119] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 2 (a) Raspberry-shaped epoxy microspheres shown.

[0120] In this embodiment, the average particle size of the microspheres measured by laser particle size analyzer is 217.5 μm, and the glass transition temperature measured by DSC is 153.4°C.

[0121] Epoxy resin strips were prepared as in Example 1, and the specific steps were as follows: 1 g of the obtained microspheres was added to 20 g of E51 monomer, the temperature was raised to 70°C, and stirred for 2 h at a speed of 120 r / min. Then, 5.2 g of curing agent IPDA was added and stirred for 5 min. The prepared epoxy resin reaction solution was poured into a mold preheated at 80°C, placed in an oven, and cured by heating at 80°C × 1h + 100°C × 1h + 130°C × 1h, and naturally cooled to room temperature to obtain modified epoxy resin strips.

[0122] According to the requirements of GB / T1040.4-2006, the tensile properties and impact properties of epoxy resin specimens were measured, and 5 samples were tested each time and the average value was taken. The epoxy resin without adding particles was used as a blank sample. The test results are shown in Table 1.

[0123] As shown in Table 1, compared with the blank sample without microspheres, the impact strength of the epoxy resin with microspheres added is increased by 23%, the tensile strength is increased by 19%, and the elongation at break is increased by 43%.

[0124] Example 7

[0125] This embodiment provides the preparation of multi-structural functional epoxy resin microspheres and their toughening and strengthening effects in cement.

[0126] 1. Preparation

[0127] As in Example 1, except that in the process of preparing microspheres, the surfactant PVP used is 1.4 g, and 3 mL of ethanol is added to obtain a mixture A; 3 mL of ethanol is added to E51 to obtain a mixture B; 3 mL of ethanol is added to DDM to obtain a mixture C. The specific steps are as follows:

[0128] S1. Add 1.4g PVP and 3g ethanol to a centrifuge tube to obtain mixture A; add 4g epoxy resin E51 to a centrifuge tube, add 3g ethanol and mix, and heat to 50°C to obtain mixture B; add 1.4g curing agent DDM to a centrifuge tube, add 3g ethanol to dissolve DDM, and obtain mixture C;

[0129] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 3 Porous epoxy microspheres shown.

[0130] In this embodiment, the average particle size of the microspheres analyzed by a laser particle size analyzer is 135.7 μm, and the glass transition temperature thereof measured by DSC is 168° C.

[0131] 2. Cement toughening and strengthening

[0132] The epoxy resin microspheres prepared above are used to toughen cement, and the specific steps are as follows:

[0133] Add 3 g of the obtained microspheres to 30 g of grade G cement ash, add 13 mL of water, and shake and homogenize for 10 minutes to obtain cement slurry; pour 5 parallel samples into molds, put them into a hydrothermal kettle, cure them in a 95°C oven for 1 day, and then cure them in 95°C constant temperature water for 6 days to obtain 5 parallel cement stone blocks.

[0134] The uniaxial compression and three-point bending mechanical properties of cement were determined according to GB / T 19139-2012. Five samples were tested each time and the average value was taken. Cement without particles was used as a blank sample. The test results are shown in Table 2.

[0135] It can be seen from Table 2 that compared with the blank sample without microspheres, the compressive strength of the cement paste with microspheres increased by 16%, the flexural strength increased by 57%, the ultimate strain increased by 113%, and the toughness modulus increased by 72%.

[0136] Example 8

[0137] As in Example 1, in the process of preparing microspheres, the surfactant used is PVP (2.8 g), and a stabilizer SiO2 nanosheet (0.3 g) is added, and the curing agent is DETDA (0.8 g). The specific steps are as follows:

[0138] S1. Add 2.8g PVP and 0.3g stabilizer SiO2 nanosheets (containing epoxy groups on the surface, 2×30μm×10nm) into a centrifuge tube, add 20mL ethanol to obtain mixture A; add 4g epoxy resin E51 into a centrifuge tube, add 8mL ethanol to mix, and heat to 50°C to obtain mixture B; add 0.8g curing agent DETDA into a centrifuge tube, add 12mL ethanol to dissolve DETDA, and obtain mixture C;

[0139] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 2 (b) Raspberry-shaped epoxy microspheres shown.

[0140] In this embodiment, the average particle size of the microspheres analyzed by a laser particle size analyzer is 41.9 μm, and the glass transition temperature thereof measured by DSC is 1411°C.

[0141] Prepare cement stone as in Example 7, add 5 parts of microspheres, and the specific steps are as follows:

[0142] 1.5 g of the obtained microspheres were added to 30 g of grade G cement ash, and 13 mL of water was added, and the mixture was shaken and homogenized for 10 min to obtain cement slurry; 5 parallel samples were poured into pre-prepared molds, placed in a hydrothermal kettle, cured in an oven at 95 °C for 1 day, and then cured in constant temperature water at 95 °C for 6 days to obtain 5 parallel cement stone blocks.

[0143] The uniaxial compression and three-point bending mechanical properties of cement were determined according to GB / T 19139-2012. Five samples were tested each time and the average value was taken. Cement without particles was used as a blank sample. The test results are shown in Table 2.

[0144] It can be seen from Table 2 that compared with the blank sample without microspheres, the compressive strength of the cement paste with microspheres increased by 40%, the flexural strength increased by 29%, the ultimate strain increased by 120%, and the toughness modulus increased by 21%.

[0145] Example 9

[0146] As in Example 1, except that in the process of preparing microspheres, the surfactant used is PVP, and PVP is dissolved in 20 mL of ethanol and 25 mL of water to obtain a mixture A; E51 is mixed with 8 mL of ethanol and 12 mL of water, and heated to 50° C. to obtain a mixture B; the curing agent is DTDA (0.8 g) and TETA (0.2 g), and 5 mL of n-hexane is added to obtain a mixture C. The specific steps are as follows:

[0147] S1. Add 5.6g PVP, 20mL ethanol and 25mL water to a centrifuge tube to obtain mixture A; add 4g epoxy resin E51 to a centrifuge tube, add 8mL ethanol and 12mL water to mix, and heat to 50°C to obtain mixture B; add curing agent 0.8g DTDA and 0.2g TETA to a centrifuge tube, add 5mL n-hexane to dissolve, and obtain mixture C;

[0148] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 4 The half-air snowman-shaped epoxy microspheres are shown.

[0149] In this embodiment, the average particle size of the microspheres analyzed by a laser particle size analyzer is 1116.3 μm, and the glass transition temperature thereof measured by DSC is 147.6°C.

[0150] Prepare cement stone as in Example 7, add 8 parts of microspheres, and the specific steps are as follows:

[0151] Add 2.4 g of the obtained microspheres to 30 g of grade G cement ash, add 13 mL of water, and shake and homogenize for 10 minutes to obtain cement slurry; pour 5 parallel samples into pre-prepared molds, put them into a hydrothermal kettle, cure them in a 95°C oven for 1 day, and then cure them in 95°C constant temperature water for 6 days to obtain 5 parallel cement stone blocks.

[0152] The uniaxial compression and three-point bending mechanical properties of cement were determined according to GB / T 19139-2012. Five samples were tested each time and the average value was taken. Cement without particles was used as a blank sample. The test results are shown in Table 2.

[0153] It can be seen from Table 2 that compared with the blank sample without microspheres, the compressive strength of the cement paste with microspheres increased by 36%, the flexural strength increased by 30%, the ultimate strain increased by 140%, and the toughness modulus increased by 80%.

[0154] Example 10

[0155] As in Example 1, except that in the process of preparing microspheres, the surfactant used is PVP, and PVP is dissolved in 20 mL of ethanol and 25 mL of water to obtain a mixture A; E51 is mixed with 8 mL of ethanol and 12 mL of water, and heated to 50° C. to obtain a mixture B; the curing agent used is DDM (1 g), and 5 mL of n-hexane is added to obtain a mixture C; the specific steps are as follows:

[0156] S1. Add 5.6g PVP, 20mL ethanol and 25mL water to a centrifuge tube to obtain mixture A; add 4g epoxy resin E51 to a centrifuge tube, add 8mL ethanol and 12mL water to mix, and heat to 50°C to obtain mixture B; add 1g curing agent DDM to a centrifuge tube, add 5mL n-hexane to dissolve DDM, and obtain mixture C;

[0157] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 5 Hollow epoxy microspheres shown.

[0158] In this embodiment, the average particle size of the microspheres analyzed by a laser particle size analyzer is 753.4 μm, and the glass transition temperature thereof measured by DSC is 158.8°C.

[0159] Prepare cement stone as in Example 7, add 6 parts of microspheres, and the specific steps are as follows:

[0160] 1.8 g of the obtained microspheres were added to 30 g of grade G cement ash, and 13 mL of water was added, and the mixture was shaken and homogenized for 10 min to obtain cement slurry; 5 parallel samples were poured into pre-prepared molds, placed in a hydrothermal kettle, cured in a 95°C oven for 1 day, and then cured in 95°C constant temperature water for 6 days to obtain 5 parallel cement stone blocks.

[0161] The uniaxial compression and three-point bending mechanical properties of cement were determined according to GB / T 19139-2012. Five samples were tested each time and the average value was taken. Cement without particles was used as a blank sample. The test results are shown in Table 2.

[0162] It can be seen from Table 2 that compared with the blank sample without microspheres, the compressive strength of the cement paste with microspheres increased by 24%, the flexural strength increased by 45%, the ultimate strain increased by 160%, and the toughness modulus increased by 57%.

[0163] Embodiment 11

[0164] As in Example 1, except that in the process of preparing microspheres, the surfactant used was PVP (5.6 g), the stabilizer was SiO2 nanoparticles (0.06 g), 25 mL of water was added to obtain a mixture A; E51 was mixed with 8 mL of ethanol and 12 mL of water, and heated to 50° C. to obtain a mixture B; the curing agent used was DDM (1 g), and 5 mL of n-hexane was added; the specific preparation was as follows:

[0165] S1. Add 5.6g PVP and 0.06g stabilizer SiO2 nanoparticles (containing epoxy and hydroxyl groups on the surface, 20nm) into a centrifuge tube, add 25mL water to obtain mixture A; add 4g epoxy resin E51 into a centrifuge tube, add 8mL ethanol and 12mL water to mix, and heat to 50°C to obtain mixture B; add 1g curing agent DDM into a centrifuge tube, add 5mL n-hexane to dissolve DDM, and obtain mixture C;

[0166] S2. Add mixture A to a three-necked flask, start mechanical stirring at a speed of 500 r / min, heat the water bath to 90°C, then add mixtures B and C, add 0.2 g of catalyst DBU, react for 6 h, cool naturally, centrifuge, then wash with ethanol, centrifuge 3 times and dry to obtain a surface containing amino, hydroxyl, as shown in FIG. Figure 6 Raspberry-shaped hollow epoxy microspheres are shown.

[0167] In this embodiment, the average particle size of the microspheres measured by laser particle size analyzer is 537.5 μm, and the glass transition temperature measured by DSC is 154.2°C.

[0168] Prepare cement stone as in Example 7, add 6 parts of microspheres, and the specific steps are as follows:

[0169] 1.8 g of the obtained microspheres were added to 30 g of grade G cement ash, and 13 mL of water was added, and the mixture was shaken and homogenized for 10 min to obtain cement slurry; 5 parallel samples were poured into pre-prepared molds, placed in a hydrothermal kettle, cured in a 95°C oven for 1 day, and then cured in 95°C constant temperature water for 6 days to obtain 5 parallel cement stone blocks.

[0170] The uniaxial compression and three-point bending mechanical properties of cement were determined according to GB / T 19139-2012. Five samples were tested each time and the average value was taken. Cement without particles was used as a blank sample. The test results are shown in Table 2.

[0171] It can be seen from Table 2 that compared with the blank sample without microspheres, the compressive strength of the cement paste with microspheres increased by 26%, the flexural strength increased by 43%, the ultimate strain increased by 193%, and the toughness modulus increased by 72%.

[0172] Table 1 Mechanical properties of different epoxy resin specimens

[0173]

[0174]

[0175] Table 2 Mechanical properties of different cement paste samples

[0176]

[0177] It can be seen from the above embodiments that when the epoxy resin microspheres obtained by the present invention are used to toughen epoxy resin and cement, their toughness and strength can be improved at the same time. This may be because the present invention uses dispersion, emulsion and Pickering emulsion polymerization methods to prepare epoxy resin microspheres, does not use toughening monomers, and uses monomers containing 2-4 epoxy groups and curing agents such as aromatic amines and fatty amines to obtain epoxy microspheres with high crosslinking degree (high Tg, 124-168°C, high strength, and certain toughness), functional groups on the surface, and porous, hollow, multi-convex raspberry-shaped or half-air snowman-shaped epoxy microspheres. When used for epoxy and cement toughening, the high cross-linking and high strength of the microspheres ensure the strength of the epoxy. The surface functional groups can be firmly bonded to the substrate through chemical reactions. At the same time, the holes and protrusions on the surface allow the microspheres to form a mechanical interlock with the substrate, which can strengthen the interaction between the microspheres and the substrate. When subjected to impact, the microspheres can absorb the impact energy through their own toughness and cracks. At the same time, they can also induce a large number of interfacial silver lines and form a pinning effect to prevent stress transmission, thereby achieving the effect of improving the toughness of epoxy and also improving the strength. When using SiO2 nanoparticles and nanosheets to prepare microspheres, the hard SiO2 nanoparticles and sheets on the surface of the microspheres act as a hard phase, improving the strength of the composite material, and can also produce cavitation to improve toughness.

[0178] The present invention has been described in detail above. For those skilled in the art, without departing from the purpose and scope of the present invention, can implement the present invention in a wider range under equivalent parameters, concentrations and conditions. Although the present invention provides specific embodiments, it should be understood that the present invention can be further improved. In a word, according to the principle of the present invention, the application is intended to include any changes, uses or improvements to the present invention, including departing from the disclosed scope in the application and the changes made with conventional techniques known in the art.

Claims

1. A method for preparing epoxy resin microspheres, comprising the following steps: The mixture A, the mixture B and the mixture C are reacted under the action of a catalyst to obtain the multi-structure functional epoxy resin microspheres; The mixture A is prepared by dispersing or dissolving a surfactant in a solvent A, or by dispersing or dissolving a surfactant and a stabilizer in a solvent A; The mixture B is prepared by mixing epoxy resin and solvent B and then heating; The mixture C is prepared by dissolving a curing agent in a solvent C.

2. The method for preparing epoxy resin microspheres according to claim 1, characterized in that: The multi-structure functional epoxy resin microspheres include non-porous, porous, hollow, raspberry-shaped or half-hollow snowman-shaped epoxy resin microspheres; The epoxy resin microsphere surface contains one or two of amino, hydroxyl and epoxy groups, but not both amino and epoxy groups; The particle size of the multi-structure functional epoxy resin microspheres is 7.3 to 1116 μm; The glass transition temperature Tg of the multi-structure functional epoxy resin microspheres is 124-168°C.

3. The method for preparing epoxy resin microspheres according to claim 1 or 2, characterized in that: The epoxy resin is selected from at least one of a diepoxy monomer, a triepoxy monomer and a tetraepoxy monomer; Based on 100 parts by mass of the epoxy resin, the mass fraction of the triepoxy monomer or the tetraepoxy monomer is 0 to 10 parts; The diepoxy monomer is preferably bisphenol A diglycidyl ether E51 or E44; The triepoxy monomer is preferably trimethylolpropane triglycidyl ether; The tetraepoxy monomer is preferably 4,4-diaminodiphenylmethane tetraglycidylamine.

4. The method for preparing epoxy resin microspheres according to any one of claims 1 to 3, characterized in that: The surfactant is a nonionic surfactant, including one of polyvinyl pyrrolidone, polyvinyl alcohol and benzene resin; When only a surfactant is added to the mixture A, the mass fraction of the surfactant is 35 to 140 parts based on 100 parts by mass of the epoxy resin; The stabilizer is a SiO2 nanoparticle or nanosheet having amino groups, epoxy groups or hydroxyl groups on the surface; When a surfactant and a stabilizer are added to the mixture A at the same time, based on 100 parts by mass of the epoxy resin, the mass fractions of the surfactant and the stabilizer are 35 to 140 parts, and the mass fraction of the stabilizer is 0.08 to 1.6 parts.

5. The method for preparing epoxy resin microspheres according to any one of claims 1 to 4, characterized in that: The curing agent is a polyamine curing agent, selected from one or more of vinylamine, polyetheramine, alicyclic amine, aromatic amine and a disulfide bond-containing curing agent; The acetamide is preferably triethylenetetramine; The polyetheramine is preferably polypropylene glycol di(2-aminopropyl) ether; The alicyclic amine is preferably isophoronediamine; The aromatic amine is preferably 4,4'-diaminodiphenylmethane or diethyltoluenediamine; The disulfide bond-containing curing agent is preferably 4,4' disulfide diphenylamine; Based on 100 parts by mass of the epoxy resin, the mass of the curing agent is 15 to 35 parts.

6. The method for preparing epoxy resin microspheres according to any one of claims 1 to 5, characterized in that: The solvent A is an organic solvent a and / or water; The solvent B is an organic solvent b and / or water; The solvent C is an organic solvent c and / or water; The organic solvent a, the organic solvent b and the organic solvent c are organic alcohols, ketones or alkanes; the organic alcohol is preferably ethanol; the ketone is preferably acetone; the alkane is preferably n-hexane; In the solvent A, based on 100 parts by mass of the epoxy resin, the mass fraction of the organic solvent a is 0 to 493 parts, and the mass fraction of water is 0 to 625 parts, but both are not 0 at the same time; In the solvent B, based on 100 parts by mass of the epoxy resin, the mass of the organic solvent b is 78 to 493 parts, and the mass of water is 0 to 625 parts; In the solvent C, based on 100 parts by mass of the epoxy resin, the mass of the organic solvent c is 78 to 493 parts, and the mass of water is 0 to 625 parts.

7. The method for preparing epoxy resin microspheres according to any one of claims 1 to 6, characterized in that: The catalyst is a tertiary amine catalyst, including one of 1,8-diazabicycloundec-7-ene, benzyldimethylamine, and 2,4,6-tris(dimethylaminomethyl)phenol; Based on 100 parts by mass of the epoxy resin, the amount of the catalyst used is 1 to 5 parts.

8. The method for preparing epoxy resin microspheres according to any one of claims 1 to 7, characterized in that: The reaction is carried out under stirring conditions with a stirring speed of 300 to 500 rpm; The reaction temperature is 60-90°C and the reaction time is 4-6h; The preparation further comprises the following steps after the reaction is completed: centrifuging the reaction solution to collect the solid phase product, then washing with ethanol, centrifuging and drying.

9. The epoxy resin microspheres obtained by the preparation method of the epoxy resin microspheres according to any one of claims 1 to 8.

10. Use of the epoxy resin microspheres according to claim 9 in simultaneous toughening and strengthening of epoxy resin or cement.

Citation Information

Patent Citations

  • Preparation method of epoxy resin hollow microsphere

    CN102850521A

  • Self-toughening epoxy resin microsphere material

    CN107880492A

  • Toughening-modified epoxy resin microsphere material

    CN108047653A

  • Impact-resistant epoxy resin microsphere material

    CN108129605A

  • Production of micron-solid epoxy-resin microsphere containing surface active group

    CN101074311A